Pedagogical childbirth simulators: utility in obstetrics. (February 2016) - Lepage, J.; Cosson, M.; Mayeur, O.; Brieu, M.; Rubod, C.
Abstract: Simulation training is an appealing and useful addition to health facilities. Simulation centers are organized to maximize network resources. Simulation training is used for certification or recertification of health professionals and is now an integral part of the methods used in continuing professional development. Simulation has played a unique role in obstetrics. This article is a narrative review describing the different types of childbirth simulators, whether anatomical, virtual, or instrumented. The article identifies the role of each simulator in the training of obstetricians and the role of these instruments in simulation centers.